The stability and microbial contamination of bupivacaine, lidocaine and mepivacaine used for lameness diagnostics in horses. (December 2016) - Adler, D.M.T.; Cornett, C.; Damborg, P.; Verwilghen, D.R.
Highlights: Local anaesthetics (bupivacaine, lidocaine and mepivacaine) used for diagnostic analgesia in horses are extremely stable. The preservative methylparaben present in commercial solutions of lidocaine degrades over time. Local anaesthetic solutions remain sterile when stored for extended periods, even after degradation of preservative. Abstract: Local anaesthetics (LAs) are frequently used for diagnostic procedures in equine veterinary practice. The objective of this study was to investigate the physico-chemical stability and bacterial contamination of bupivacaine, lidocaine and mepivacaine used for lameness examinations in horses. The LAs were stored in 12 different groups at different temperatures (−18 °C to 70 °C), light intensities and in common veterinary field conditions for up to 16 months. The pH, presence of bacterial contamination and concentrations of LAs and methylparaben (a preservative present in lidocaine) were determined serially in both new and repeatedly punctured (RP) vials. Mepivacaine remained chemically stable. A 1.9% increase in bupivacaine concentration was evident in one group, whereas a 1.9–3.7% decrease was noted in six groups. Risk factors associated with a change in concentration were light and RP vials. Lidocaine concentration decreased 6.3% in one group and increased 5.3–7.2% in two groups. Risk factors for degradation were heat and RP vials whereas storage in practice vehicles was a risk factor for increased concentrations. Methylparaben decreased 8.3–75.0% in seven groups, and RP vials, heat and storage in practice vehicles were risk factors for degradation. No contamination was present in any of the LAs and pH remained stable. Commercially available solutions of lidocaine, mepivacaine and bupivacaine stored under common veterinary field conditions are extremely stable and sterile for extended periods. The minor changes in concentration documented in this study are unlikely to affect anaesthetic efficacy during equine lameness examinations. When using products containing methylparaben, degradation of the preservative over time is to be expected.